Investigation of SiGeSn/GeSn/SiGeSn single quantum well with enhanced well emission. (30th November 2021) - Olorunsola, Oluwatobi; Ojo, Solomon; Abernathy, Grey; Zhou, Yiyin; Amoah, Sylvester; Grant, P C; Dou, Wei; Margetis, Joe; Tolle, John; Kuchuk, Andrian; Du, Wei; Li, Baohua; et al.
Abstract: In this work, a SiGeSn/GeSn/SiGeSn single quantum well was grown and characterized. The sample has a thicker GeSn well of 22nm compared to a previously reported 9nm well configuration. The thicker well leads to: (i) lowered ground energy level in Γ valley offering more bandgap directness; (ii) increased carrier density in the well; and (iii) improved carrier collection due to increased barrier height. As a result, significantly enhanced emission from the quantum well was observed. The strong photoluminescence (PL) signal allows for the estimation of quantum efficiency (QE), which was unattainable in previous studies. Using pumping-power-dependent PL spectra at 20K, the peak spontaneous QE and external QE were measured as 37.9% and 1.45%, respectively.